De gezondheid van het kind en het veranderend perspectief van de Groningse plattelandsschoolarts (1930–1970) - Bakker, Nelleke (Studium, 2015)
The health of the child and the changing perspective of school doctors at the Groningen countryside (1930–1970) From 1948 child hygiene was supposed to include mental health. This paper discusses the way school physicians in an agrarian-industrial area of the Netherlands have adapted their activities and concerns accordingly between 1930 and 1970. In spite of an improvement of pupils’ physical health they shifted their attention only to a limited extent from physical to mental health. Nevertheless, mental health became important, as they stimulated activities they conceived of as promoting both physical and mental health, like gymnastics and swimming. However, their key interest concerned mental deficiency and the promotion of special schooling. In this respect they have played a decisive role, to the extent of producing feeblemindedness and learning disabilities. At the same time the school doctors clung to their traditional ideal of supporting the school’s effectiveness by trying to reduce dangers threatening pupils’ learning capacity and wellbeing, like too large school classes and uniform group teaching.